Tiny tough eaudiobook - Hanlon, Abby (Dory Fantasmagory, 2019)
The fifth adventure in the enormously popular Dory Fantasmagory series takes on the tried-and-true theme of childhood friendships, and turns it on its head, Dory-style. When her big sister Violet has friend trouble at school, Dory tries to come to her rescue. But, of course, Dory's active imagination takes over, and Dory's suddenly sure that Violet's problem involves pirates—and Violet's lost friendship bracelet is hidden treasure. When Dory sets sail to recover the treasure, she has to navigate rocky waters without her imaginary friend Mary, who has gone off on vacation with an exciting new friend of her own. There's a ton of treasure in Dory's fifth adventure as Dory mixes in pirates, pals (real and make-believe), and her own imagination into one wild and wet free-for-all.